Debit Air Daerah Aliran Sungai Mallusetasi pada Tahun 2022 Menggunakan Model SWAT - Zulkifli Wahda; Wahyuni Wahyuni (Pangale Journal of Forestry and Environment, 2026)
River discharge characteristics in a watershed are strongly influenced by two important factors, namely the physical conditions and rainfall on catchment area. The Mallusetasi watershed is one of the watersheds in Barru Regency that frequently experiences flooding. This study aimed to analyze the factor affecting river discharge and the flow regime coeeficient in the Mallusetasi Watershed. The research employed a quantitative descriptive method. Data collection was carried out by downloading several satellite imagery and climate datasets, followed by field observations. The obtained data were analyzed using the Soil and Water Assessment Tool (SWAT) model. The results showed that the main factors influencing discharge in the Mallusetasi Watershed were topography and soil characteristics. The watershed is predominantly characterized by steep slope classes covering a total area of 4,422.51 ha, while the soil texture is dominated by clay loam covering 6,412.59 ha. These conditions resulted in very high Flow Regime Coefficient (FRC) values in the Mallusetasi Watershed. Sub-watershed 1 had an FRC value of 155.40, Sub-watershed 2 had an FRC value of 133.24, and Sub-watershed 3 had an FRC value of 180.82. All sub-watersheds recorded FRC values greater than 110, which are classified as very high. The high FRC values indicate that the hydrological conditions of the Mallusetasi sub-watersheds are poor.